Unveiling Indonesian EFL Teachers' Intercultural Sensitivity: A Narrative Inquiry into Language Teaching Material Design - Sellina Anggieta; Sumardi Sumardi; Endang Setyaningsih (STAI Hubbulwathan Duri, 2023)
In the 21st century, the globalization impact has escalated the importance of intercultural sensitivity (IS) to societies and individuals. The new era of globalization offers new lenses for EFL teachers in developing and designing IS materials. Retrieved the importance of IS in English language teaching (ELT), this study reports a narrative study investigating how teachers conceptualized IS. This study also aims to explore teachers' conceptual understanding of IS affected them in designing ELT materials. The framework of this study applied the concept of IS proposed by Chen and Starosta (2000). The empirical data were gathered through semi-structured interviews and artifacts with three EFL teachers from a secondary school. The data was analyzed using thematic analysis by Barkhuizen, Benson, and Chik. Drawing on qualitative content analysis, the results captured that EFL teachers grasped the conceptualization of IS during English language teaching. The results also revealed that EFL teachers' understanding of IS causes them to be sensitive in designing English teaching materials. Teachers' understanding of IS concepts portrayed that teachers realized, accepted, and respected cultural differences during the intercultural instructional processes. This finding implies the need for EFL teachers to include some culturally sensitive topics or themes in their teaching materials by linking the tolerant curriculum with local cultural wisdom. This study also suggests exploring how EFL teachers developed intercultural teaching materials that provided a critical engagement with today's cultural literacies.